The Influence of Adversity Quotient, Learning Motivation, and Self-Confidence on Entrepreneurial Interest - Muna Karhani; Rita Eka Izzaty; Herwin Herwin; Karyati Karyati; Karmini Karmini; Rendi Rendi (Economics Education Department Universitas Negeri Semarang, 2025)
Entrepreneurial interest needs to grow among university students to increase the number of entrepreneurs in society. Factors such as adversity quotient, learning motivation, and self-confidence can influence entrepreneurial interest. This study aimed to determine the effect of adversity quotient, learning motivation, and self-confidence on entrepreneurial interest. The purposive sampling was used in this study. Subjects in the study were 240 students in an entrepreneurship course in the Agribusiness Study Programme, Agriculture Faculty, Mulawarman University, East Kalimantan Province, Indonesia. This study analyzed the validity and reliability of scales, test of normality, multicollinearity, and heteroscedasticity, formulated the model of multiple linear regression, F test, t test, and calculated adjusted R2. The results of this study indicate that the adversity quotient, learning motivation, and self-confidence significantly influence entrepreneurial interest. Adversity quotient and learning motivation, partially, influence very significantly on entrepreneurial interest. However, self-confidence does not have a significant influence on entrepreneurial interest. Those findings help increase people's motivation to become entrepreneurs, especially young people.